Application of multi-objective mathematical programming technique for contractor selection. (2018) - Nanda, Ankita; Acharya, Srikumar
In this paper, a multi-objective mathematical model is formulated for contractor selection problem, which is solved taking into consideration various attributes for supplying goods for a University mess in the hostel. For better mathematical model formulation factors like, past performance, financial status, product return policy, time factors etc. of contractors are considered. In order to illustrate the methodology a case of one University is considered. A mathematical model is also formulated by considering the data of the mess of the University. Finally, it is solved to select appropriate contractors using fuzzy programming method.